Connecting - Christy I. Wegner; W. Keith Duffy; Sheila Kennedy; Jen Consilio; Carl Vandermeulen; Robert Randolph (Journal of the Assembly for Expanded Perspectives on Learning, 2018)
Christy I. Wenger, The Emotional Labor of Our Work W. Keith Duffy, Interdisciplinary Dangers: A Small Caveat Sheila Kennedy & Jen Consilio, One Mindful Step Carl Vandermeulen, The Way to the Falls Robert Randolph, A Good Rain